Histone methylation regulates Hif‐1 signaling cascade in activation of hepatic stellate cells - Fei Hong; Lu Wan; Jie Liu; Ke Huang; Zhenmeng Xiao; Yingjing Zhang; Chunwei Shi (FEBS Open Bio)
Liver fibrosis is characterized by deposition of excessive extracellular matrix (ECM). The major source of ECM is activated hepatic stellate cells (HSCs). Previously, we reported that hypoxia‐inducible factor‐1 (Hif‐1) regulates activation of HSCs through autophagy. In current work, human HSC cell line LX‐2 was used as cell model. It was determined that trimethylation of H3 histone on lysine 4 (H3K4me3) occurred in the Hif‐1 transcriptional complex. Inhibition of modifications of histone methylation suppressed Hif‐1 nuclear transport, autophagosome formation, and activation of LX‐2 cells. These data suggest that histone methylation modification plays an important role in the Hif‐1 signaling cascade regulating HSC activation.